2020
DOI: 10.1177/0269215520903786
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of continuous and pulsed therapeutic ultrasound combined with exercises for knee osteoarthritis: a randomized controlled trial

Abstract: Objectives: To compare the effects of continuous and pulsed therapeutic ultrasound combined with strengthening exercises. Design: This is a double-blind randomized controlled trial. Setting: Pontifical Catholic University. Subjects: One hundred participants with Grade 2–4 knee osteoarthritis and both genders were involved. Intervention: Participants were randomized into five groups: Group I ( n = 20; in the first month, continuous ultrasound was applied), Group II ( n = 20; in the first month, pulsed ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…Of the nine trials using continuous ultrasound as a treatment, eight reduced WOMAC scores by 20%. While most studies showed favorable relative risk reductions in WOMAC, only a few studies [ 55 , 56 , 57 ] yielded clinically significant relative risk reductions in stiffness WOMAC score, with −62.5%, the relative risk reduction for pain WOMAC score being the most clinically significant [ 57 ]. Discrepancies in findings can be attributed to the combination of ultrasound application with or without rigorous exercise.…”
Section: Physical Therapy Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine trials using continuous ultrasound as a treatment, eight reduced WOMAC scores by 20%. While most studies showed favorable relative risk reductions in WOMAC, only a few studies [ 55 , 56 , 57 ] yielded clinically significant relative risk reductions in stiffness WOMAC score, with −62.5%, the relative risk reduction for pain WOMAC score being the most clinically significant [ 57 ]. Discrepancies in findings can be attributed to the combination of ultrasound application with or without rigorous exercise.…”
Section: Physical Therapy Interventionsmentioning
confidence: 99%
“…Discrepancies in findings can be attributed to the combination of ultrasound application with or without rigorous exercise. Of the trials that showed clinically meaningful results, the continuous ultrasound treatments used a 1 MHz frequency with an intensity of 1 W/cm 2 or 1.5 W/cm 2 for 5 to 10 min [ 38 , 57 , 58 ]. The pulsed ultrasound interventions similarly used a 1 MHz frequency with an intensity of 1 W/cm 2 for 10 min at a pulsed mode of 25% [ 57 , 59 ].…”
Section: Physical Therapy Interventionsmentioning
confidence: 99%
“…For example, they can both be used to improve endothelial function, alleviate pain, and improve physical disability (84)(85)(86). Continuous ultrasound produces more significant thermal effects than pulsed ultrasound when the parameters are the same (87,88). As far as we know, the therapeutic effect of low-intensity ultrasound is mainly caused by mechanical effects.…”
Section: Chondrocytesmentioning
confidence: 99%
“…US can reduce muscle spasms and pain, and facilitate tissue repair by increasing local blood flow and stimulating inflammatory mediators 26. US has been widely reported to be treatment beneficial in fracture non-unions,27 28 osteoarthritis,29 30 chronic muscle pain,31 32 soft tissue injury,33 and so on. As for tendinopathy, US is also a potential non-invasive treatment modality for frozen shoulder,34 35 rotator cuff,36 achilles37 38 and patellar39 tendinopathy.…”
Section: Introductionmentioning
confidence: 99%